Knowledge of manipulators regarding good food handling practices (Research, Society and Development, 2021)
Introduction: In the feeding unit, the handler plays a fundamental role for a safe environment and for food handling to happen with safety and quality. Objective: To analyze the level of knowledge of food handlers participating in the Course on Good Practices in Food Handling promoted by a University Center in the South Zone of São Paulo regarding good practices and hygienic-sanitary food control. Methodology: Cross-sectional study, using partial data from the research approved by the Research Ethics Committee of the Adventist University Center of São Paulo under Opinion. Data collection took place through two semi-structured questionnaires during the Training Course in Good Food Handling Practices promoted by the Nutrition Course of this University Center in May 2021. Results: 31 participants were evaluated, most of them female (87%) with a mean age of 31.6±7 years, without a formal contract (77.4%), workers in the street food trade (16.1%), and monthly income of up to 1 minimum wage (25.8%). Participants had excellent general knowledge about good practices and hygiene in food handling (80.6%) and the need for greater attention to issues related to proper temperature control and how to avoid foodborne illnesses. Conclusions: The study participants' level of knowledge of good practices was considered satisfactory, lacking more information on ways to prevent foodborne diseases, with the training course on good practices and the presence of a nutritionist being essential tools for the improvement of services.